2016
DOI: 10.1108/mip-05-2015-0090
|View full text |Cite
|
Sign up to set email alerts
|

eWOM, eReferral and gender in the virtual community

Abstract: Purpose – The purpose of this paper is to examine the influence of electronic referral (eReferral) marketing and electronic word-of-mouth (eWOM) on brand image and purchase intention, coupled with the moderating effect of gender in the relationship. Design/methodology/approach – Structural equation modeling was applied to examine the interplay between the proposed variables, using a random sample of 308 respondents in Cyprus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
4
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 74 publications
5
105
4
14
Order By: Relevance
“…eWOM Park and Lee (2009) suggested that eWOM has higher effect when a good is consumed than when it is searched, fundamentally suggesting that the impact of eWOM becomes stronger after service encounter, this position was shared by Gruen, Osmonbekov, & Czaplewski, (2006) as they suggested that eWOM leads to post-purchase customer loyalty. As against the traditional WOM communication, eWOM eliminate the negativity associated with bias information dissemination among friends, relatives and family because the identity of the reviewer cannot be identified (Abubakar, Ilkan, & Sahin, 2016). Different motivations has been found to be responsible for generating eWOM, pre-purchase expectations, customer delight, satisfaction or dissatisfaction and general consumer behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…eWOM Park and Lee (2009) suggested that eWOM has higher effect when a good is consumed than when it is searched, fundamentally suggesting that the impact of eWOM becomes stronger after service encounter, this position was shared by Gruen, Osmonbekov, & Czaplewski, (2006) as they suggested that eWOM leads to post-purchase customer loyalty. As against the traditional WOM communication, eWOM eliminate the negativity associated with bias information dissemination among friends, relatives and family because the identity of the reviewer cannot be identified (Abubakar, Ilkan, & Sahin, 2016). Different motivations has been found to be responsible for generating eWOM, pre-purchase expectations, customer delight, satisfaction or dissatisfaction and general consumer behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We adapted 6-item scale used by prior studies (Jalilvand & Samiei, 2012a;Abubakar, Ilkan, & Sahin, 2016). A sample item for eWOM was: "If I don't read tourists' online travel reviews when I travel to a medical destination, I worry about my decision".…”
Section: Ewommentioning
confidence: 99%
“…Additionally, it is considered very persuasive, which can be partially explained by its perceived credibility and trustworthiness (Chatterjee, 2001). As such, the brands are particularly motivated to understand the eWOM, because the conventional forms of communication appear to be losing its effectiveness (Abubakar et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Influence marketing therefore does not only involve getting the largest number of followers or the highest level of interaction but also in making the consumer an influencer, identifying the context that leads to their purchasing decisions. Thus, according to Abubakar et al (2016), purchase intention is influenced not only by the product value and benefits, but also by testimonies from other consumers.…”
Section: The Influence and Contents Of Fashion And Beauty Blogsmentioning
confidence: 99%
See 1 more Smart Citation